Fieldwork is not just leisure: an unique methodological resource in the teaching-learning process in geography - Farias, Ricardo Chaves de; Silva, Alcinéia de Souza (Revista Ensino de Geografia (Recife), 2021)
Starting from the systematization of a method for the development of fieldwork in Basic Education, the article discusses the potential of this methodological resource in the teaching-learning process in Geography. For this purpose, the theoretical discussion of a critical nature and participant observation in a work carried out in the municipality of Pirenópolis-GO constitute the methodological procedures employed in this study. The results show that, based on a method that ensures the pedagogical development of this practice and on theoretical contributions that favor the understanding of the spatiality of facts/phenomena, fieldwork is an effective instrument in the construction of geographical knowledge. It is noteworthy that its purpose is educational and enables geographic reasoning through practical and mental activities in relation to the objects / phenomena studied.